Democratizing effects of digital ledger technologies: Implications for economic mobility - Makridis, Christos A.; Liao, Gordon Y. (Frontiers in Blockchain, 2023)
There is a large body of empirical and theoretical literature on the effects of technological change on individuals, labor markets, and overall economic activity. Theories of skill-biased technical change (SBTC) suggest that technology increases the earnings power of skilled workers, but substitutes for less skilled workers. Distributed ledger technologies (DLTs) provide a new context for examining and understanding the impact of technology change on labor, competition, and economic outcomes. This paper explores the theoretical frameworks through which DLTs could enhance economic mobility and provides examples from several areas, including: (i) the creation of new jobs and higher value-added jobs, and the modularization of complex tasks; (ii) improvements in the way people learn and acquire human capital; (iii) increased competition in the marketplace; and (iv) more inclusive access to financial services with fewer intermediaries.